The effectiveness of supportive therapy on psychological capital and post traumatic growth in women with multiple sclerosis - Ebrahimi, Soheila; Khodabakhsh, Ahmad; Farokhi, Norali (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Multiple sclerosis is a neurological and progressive disease. Living with MS has many negative and positive effects on patients' physical and mental health. This study aimed to investigate the effect of supportive therapy on post-traumatic growth and psychological capital in women with MS. Methods: This study used quasi-experimental method (a pretest-posttest and fallow up plan with a control group). Participants consisted of 30 women with MS who were selected using convenience sampling method and were randomly divided into two groups of experimental and control groups. The measuring tool was psychological capital questionnaire (2007) and post-traumatic growth questionnaire (1996) which was completed by the participants. Then, the participants in the experimental group participated in 10 sessions of 50 min of intervention based on Winston, Rosenthal, & Pinsker (2004) supportive therapy protocol. Repeated-measures mixed-model analysis of variance (ANOVA) was used to analyze data. Results: Data analysis showed that supportive therapy had significantly increased the psychological capital (F=16/50, P≤ 0/001) and post traumatic growth (F=14/40, P≤ 0/001) in the experimental group, compared to the control group and the effects of intervention over time remained constant. Conclusion: Based on the findings of this study, supportive therapy can be an effective intervention to increase psychological capital and post traumatic growth in MS patients and can be used to improve the psychological state and better cope with the disease.